1971
DOI: 10.1037/h0031770
|View full text |Cite
|
Sign up to set email alerts
|

The prediction of performance for black and for white police patrolmen.

Abstract: This is a report on some considerations involved in validating an occupational test battery for a racially mixed group. The 75% white and 25% black sample showed clear-cut differences in performance on the predictor variables and ambiguous differences in performance on the criterion variables. Cross-validations demonstrated that poorest prediction coefficients (sometimes 0 or negative) resulted when predicting across the racial groups using the same prediction equation for members of both groups. Predictions i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1973
1973
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…In such cases, criterion data were collected in a way that artificially expands the range of performance. Data from one study (Baehr, Saunders, Froemel, & Furcon, 1971) were excluded because the researchers purposely sampled police incumbents from the upper and lower thirds of performance distributions, which would lead to overestimates of racial mean effect sizes.…”
Section: Methodsmentioning
confidence: 99%
“…In such cases, criterion data were collected in a way that artificially expands the range of performance. Data from one study (Baehr, Saunders, Froemel, & Furcon, 1971) were excluded because the researchers purposely sampled police incumbents from the upper and lower thirds of performance distributions, which would lead to overestimates of racial mean effect sizes.…”
Section: Methodsmentioning
confidence: 99%
“…This state of affairs does not practically reflect typical personnel selection situations. Precluding studies with range enhancement meant that Baehr et al (1971) could not be used in analyses. This is a judgment call in meta-analysis, and we note that this study was used by J. K. Ford et al (1986).…”
Section: Criteria For Inclusionmentioning
confidence: 99%
“…Previous research on police personality has indicated that emotional stability is a crucial factor in determining the probability of success of a policeman (Baehr, Saunders, Froemel, & Furcon, 1971). However, a considerable amount of research indicates that policemen may, in fact, be neurotic or even psychotic (Bain, 1939;Herman, 1971;Bohardt, 19S9;Kates, 19SO;Rankin, 1959;Rapaport, 1949;Skolnick, 1966;Westley, 1951;Zion, 1966).…”
mentioning
confidence: 99%
“…(which finds less neuroticism among police groups than is found in the general population) indicates that the intensive screening of police applicants, advertently or inadvertently, eliminates many neurotics. Because of the finding byBaehr et al (1971) that emotional stability was a crucial factor in predicting good police performance, the authors believe that rigorous screening for neuroticism should be a part of police selection procedures.…”
mentioning
confidence: 99%